PERAN PANGKALAN PENDARATAN IKAN (PPI) INENGO TERHADAP PENDAPATAN NELAYAN DI DESA HUANGOBOTU KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO - Mamuki, Emiliyan; Yapanto, Liz M.; Abbas, Defriyanti N. (Jurnal Perikanan Pantura (JPP), 2023)
This research was conducted in February to August 2023 in PPI Inengo, Huangobotu village, Kabila Bone sub district, Bone Bolango Regency. The sample that applied in this research are 34 fisherman with sampling technique purpose sampling which sampling technique taking based on specific criteria or targets. This research aimed to knows the role of the fish landing station (PPI) Inengo of fishing revenues in Huangobotu Village, Kabila bone sub-district, Bone Bolango Regency. However, the author in method of this research used the survey method and observation directly. In addition, the data obtained then analyzed the data in descriptive qualitative and quantitative. The research result was showed that the incidental landfill (PPI) has important role in fisherman income. Hence, based on Likert scale showed that 116 rating scores in 91-120 rating score which means that the presence of PPI Inengo was very influential on fisherman income.